Developing and assessing intercultural communicative competence : a guide for language teachers and teacher educators - Lázár, Ildikó; éCaénková, Michaela (Languages for social cohesion = Les langues pour la cohésion sociale, 2007)
Many language teachers, teacher educators and second language acquisition researchers have expressed the conviction that the primary aim of foreign language teaching is to enable learners to communicate with people from different linguistic and cultural backgrounds in an increasingly multicultural world. The aim of this publication is to assist teacher educators and language teachers in shifting the focus from linguistic competence to intercultural communicative competence. The printed booklet of the present guide contains the introductions to: • definitions of key terms in intercultural communication; • planning and designing intercultural communication courses and workshops; • teaching/training methods and materials; • assessing intercultural communicative competence. The materials on the accompanying CD-Rom include: • the theoretical background to teaching language and culture; • detailed workshop and course planning guidelines; • teaching materials and activities based on literature, films and songs; • guidelines and tasks for assessment and descriptors of competences; • intercultural communication workshop reports; • our research articles about the intercultural dimension of FIT. All of the materials in this publication are based on our research and the lessons we learnt from the training sessions we held in 12 European countries within the framework of the ICCinTE project of the ECML between 2004 and 2006. This guide can be used independently or it can complement our intercultural communication textbook Mirrors and windows in order to help incorporate intercultural communication training into foreign language teaching and teacher education more systematically.